2013
DOI: 10.1093/ejcts/ezt580
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative graft verification in coronary surgery: increased diagnostic accuracy adding high-resolution epicardial ultrasonography to transit-time flow measurement

Abstract: HR-ECUS should be considered complimentary to TTFM. Simultaneous use of the two methods during CABG provides morphological and functional information improving considerably diagnostic accuracy of intraoperative graft verification procedure close to 100%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 23 publications
1
58
0
Order By: Relevance
“…Many reports in literature demonstrated that severity of coronary artery stenosis, TTFM parameters, and severity of to and fro flow on TTFM were risk factors for further graft failure [19][20][21][22][23][24]. In the present study, we found major four types of the flow dynamics.…”
Section: The Relationship Between Hems Parameters and Cag Outcomesupporting
confidence: 63%
See 1 more Smart Citation
“…Many reports in literature demonstrated that severity of coronary artery stenosis, TTFM parameters, and severity of to and fro flow on TTFM were risk factors for further graft failure [19][20][21][22][23][24]. In the present study, we found major four types of the flow dynamics.…”
Section: The Relationship Between Hems Parameters and Cag Outcomesupporting
confidence: 63%
“…TTFM and high-frequency epicardial ultrasound have been used as popular tools in CABG [15][16][17][18][19][20][21][22][23][24]. Likewise, ICG-AG has been commonly used for evaluating graft patency.…”
Section: Discussionmentioning
confidence: 99%
“…The TTFM console we currently use in the preclinical animal study disposes of epicardial ultrasound imaging. If there is still uncertainty regarding the quality of the anastomosis after the flow measurements, a real-time epicardial ultrasound image can be of great help in further evaluation of the anastomosis, hereby increasing the diagnostic accuracy [27][28][29][30][31] .…”
Section: Discussionmentioning
confidence: 99%
“…Indocyanine green fluoroscopy and transit-time ultrasound flowmetry are validated and easy to use means of identifying graft errors and surgical correction intraoperatively [8,[15][16][17][18][19]. However, they pose potential risks to the patient by prolonging cross-clamp and cardiopulmonary bypass times, and they may theoretically could lead to poorer anastomosis quality and patency by inappropriate revision.…”
Section: Detection Of Graft Failurementioning
confidence: 99%